1986
DOI: 10.1111/j.2042-7158.1986.tb04594.x
|View full text |Cite
|
Sign up to set email alerts
|

Activities of novel polyhydroxylated cardiotonic steroids purified from nuchal glands of the snake, Rhabdophis tigrinus

Abstract: Seven novel polyhydroxylated steroids were isolated from the nucho-dorsal glands of the snake, Rhabdophis tigrinus. Biological activities of these steroids in inhibiting (Na+ + K+)ATPase and in producing positive inotropic action were examined in comparison with those of ouabain and gamabufotalin. Gamabufotalin was approximately 10 times more potent than ouabain in inhibiting (Na+ + K+)ATPase. Two compounds, compounds III and XIII, of the seven, produced nearly equipotent enzyme inhibitory activity to ouabain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Regardless of the reason for the pattern, it may be beneficial to hatchling R. tigrinus to have gamabufotalin as their dominant bufadienolide. This compound is approximately 10 times more effective at inhibiting the sodium-potassium pump in canine kidney than ouabain (Azuma et al 1986), and thus may be more effective as an antipredator compound than other bufadienolides. However, the physiological activities of most of the other bufadienolides remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the reason for the pattern, it may be beneficial to hatchling R. tigrinus to have gamabufotalin as their dominant bufadienolide. This compound is approximately 10 times more effective at inhibiting the sodium-potassium pump in canine kidney than ouabain (Azuma et al 1986), and thus may be more effective as an antipredator compound than other bufadienolides. However, the physiological activities of most of the other bufadienolides remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…103 In vitro toxicity studies using mammalian kidney and heart preparations demonstrated that bufadienolides in the secretions inhibit (Na + + K + ) ATPase and are positively inotropic, 104 which are typical properties of these compounds.…”
mentioning
confidence: 99%
“…In dendrobatids, hydroxylation dramatically increases the toxicity of a sequestered alkaloid (7). The bufadienolides in R. tigrinus that have been studied for activity vary widely in their inhibition of the sodium-potassium pump and their positive inotropic action on heart muscle (29), which may be in part due to differences in hydroxylation among compounds. Hydroxylation may also influence the bioavailability of bufadienolides.…”
Section: Discussionmentioning
confidence: 99%